2015
DOI: 10.5152/imj.2014.13284
|View full text |Cite
|
Sign up to set email alerts
|

Extralobar Pulmonary Sequestration in a Neonate

Abstract: Congenital pulmonary sequestration (CPS) is a type of thoracic malformation that may be represented as a solid or cystic mass composed of nonfunctioning primitive tissue. It does not interact with the tracheobronchial tree and has unusual systemic blood supply. Various congenital malformations may be presented with CPS. More than one-half of CPS cases are diagnosed in later childhood or even in adulthood. Neonates and infants are usually asymptomatic, and they are usually diagnosed due to the presence of other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Following the analysis of data containing the project specifications of the building in a simulation environment, a comparison was made between the energy performance of the building based on the ASHRAE version and the energy loads for heating and cooling as well as lighting loads, as outlined in the preliminary design of the building. The system parameters identified for reducing the energy demand and improving the energy efficiency of the sample building are present in tables (1)(2)(3)(4).…”
Section: Study Area and Data Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the analysis of data containing the project specifications of the building in a simulation environment, a comparison was made between the energy performance of the building based on the ASHRAE version and the energy loads for heating and cooling as well as lighting loads, as outlined in the preliminary design of the building. The system parameters identified for reducing the energy demand and improving the energy efficiency of the sample building are present in tables (1)(2)(3)(4).…”
Section: Study Area and Data Usedmentioning
confidence: 99%
“…In a study conducted by Mirrahimi et al [2016] it was found that a significant correlation exists between different building elements, including shading devices, external walls, external roofs, external glazing, as well as insulation, and the reduction of energy consumption. Ozturk [2015] provided information on green buildings and their evaluation standards of them, which are significant applications in terms of energy efficiency. Turker [2010] developed a method for green building rating systems and applied an analysis of global green building rating systems using the example of the Erzurum shopping centre.…”
Section: Introductionmentioning
confidence: 99%
“…These books can be used for understanding Gezi Park Protest from different perspectives. (Abat et al 2014;Acar 2014;Celebi and Soysal 2013;Kongar and Kucukkaya 2013;Ozbank 2013;Ozturk 2013).…”
Section: Gezi Park Protestsmentioning
confidence: 99%